Small ruminant feed production in a farming systems context - Sumberg, J.E. (International Livestock Centre for Africa, 1984)
Describes ILCA's research w. integrated alley farming, Gliricidia & Leucaena w. food crops, in southwest Nigeria, either w. a cut-and-carry browse feeding system for both sheep & goats or a grazed fallow system for sheep, outlining its biological & economic advantages and assessing its applicability in other parts of West Africa.